2010
DOI: 10.1007/s12094-010-0519-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of an electron spoiler for radiation treatment of surface skin diseases

Abstract: The feasibility of using a low-energy electron beam with a spoiler for treating surface skin diseases was demonstrated. The method is hygienic and avoids some of the disadvantages associated with the bolus technique, but it is valid only for flat surfaces and perpendicular incidence. As a consequence, it can be an alternative to bolus and other reported methods in certain cases, especially when a particular sterility assurance level is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
2
8
0
Order By: Relevance
“…The method consists in adding an aluminium spoiler at the end of the electron applicator, which results in an optimal radiation beam for skin irradiation. 20 Historically, beam spoilers have been employed in photon therapy to increase the build-up dose near the surface, but their use in conjunction with electron beams in clinical practice after surgery has not been previously evaluated. 20 Between 2007 and 2012, our institution treated 20 keloids in 19 patients using this modality.…”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…The method consists in adding an aluminium spoiler at the end of the electron applicator, which results in an optimal radiation beam for skin irradiation. 20 Historically, beam spoilers have been employed in photon therapy to increase the build-up dose near the surface, but their use in conjunction with electron beams in clinical practice after surgery has not been previously evaluated. 20 Between 2007 and 2012, our institution treated 20 keloids in 19 patients using this modality.…”
Section: Aimmentioning
confidence: 99%
“…20 Historically, beam spoilers have been employed in photon therapy to increase the build-up dose near the surface, but their use in conjunction with electron beams in clinical practice after surgery has not been previously evaluated. 20 Between 2007 and 2012, our institution treated 20 keloids in 19 patients using this modality. 21 In what follows, we evaluate our clinical results and discuss them in the light of the existing literature.…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…McKenzie et al used a plastic spoiler in order to match two adjacent electron fields [ 11 ]. Hernández et al studied the application of aluminum spoilers for increasing surface dose of a 6 MeV electron beam [ 12 ]. So-Yeon Park et al compared dosimetry characteristics of a 4 MeV electron beam without spoiler to a 6 MeV electron beam with spoiler [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, using bolus on sloped surfaces and partly bloused fields can cause remarkable dose perturbations and may also produce cold and hot spots below the edge. An alternative is to use an electron beam spoiler to decrease the electron therapeutic depth while increasing the surface dose [ 12 , 15 ]. Studies have revealed that for every treatment unit and for each spoiler material, it is necessary to determine the optimum spoiler thickness by considering the energy of electron beam, depth of tumor and tumor lateral expansion.…”
Section: Introductionmentioning
confidence: 99%